Green hydrogen value chain challenges and global readiness for a sustainable energy future - Vedant Singh; Aishwarya V.M.; Sriprasath V.J.; Pranavi M.; Kavya Rao N.; Tej Singh (iScience)
Summary: Green hydrogen (GH) offers a sustainable fuel alternative for addressing global energy and climate goals. This study evaluates GH viability across five dimensions: technological advancement, economic feasibility and market potential, environmental impacts and resources dynamics, policy regulatory frameworks, and interdisciplinary collaborations. Recent advancements in electrolysis technologies and artificial intelligent driven process optimization have enhanced production efficiency and resource management. Despite increasing investments, GH faces challenges such as high electricity demand, water usage, and infrastructure constraints. A regional assessment using the Green Hydrogen Feasibility Index (GHFI) indicates that countries such as China, Germany, and the USA lead in readiness due to robust policies and investment, while others face implementation issues. The finding emphasizes the need for coordinated global regulation, infrastructure development, and digital integration to enhance GH scalability and sustainability. This work contributes a comprehensive framework for assessing GH deployment and highlights strategies to accelerate its role in achieving a net-zero energy future.